CLICKING OR SKIPPING? UNDERSTANDING WHY PUNJAB’S CONSUMERS HESITATE TO EMBRACE SOCIAL MEDIA MARKETING OF ELECTRONIC GADGETS - Khanna, Bala; Sood, Sarita (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study looks into the difficulties Punjabi consumers faced when implementing social media marketing for electronic devices. Using a purposive sample approach and a quantitative research design, 400 active social media users who have bought electronics through different online retailers were surveyed for the study. The results indicate notable variations in the difficulties associated with usability, reliability of data, and safety, contingent on the distinct media kinds that consumers favour. Perceived challenges on social networking sites are higher, especially when it comes to authenticity and ease of use. The managerial implications highlight the significance of user experience, information authenticity, and security measures, and recommend customised strategies to address platform-specific challenges. The study ends with recommendations for further research that emphasise the need to investigate new social media platforms, the impact of demographic and cultural variables, and the efficacy of consumer adoption-boosting interventions in Punjab's dynamic electronic device market.